Pengaruh Tingkat Suku Bunga, Tingkat Bagi Hasil, Likuiditas, Inflasi, Ukuran Bank, dan Pertumbuhan Produk Domestik Bruto terhadap Deposito Mudharabah Bank Umum Syariah di Indonesia - Akhris Fuadatis Sholikha (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2018)
The purpose of this study is to examine the influence of interest rates, the level of profit sharing, liquidity, inflation, the size of the company, and the growth of gross domestic product simultaneously and partially on mudaraba deposits at Islamic Commercial Banking in Indonesia. This study conduct quantitative research with hypothesis testing on secondary data in term of time series on the quartely financial statements starting from the first quarter of 2011 to fourth quarter of 2014. The reserach sample is six Islamic Commercial Banking in Indonesia. The data analysis technique in this study are descriptive analysis, classical assumption test, multiple regression analysis, hypothesis test uses F test, and t test. The result showed that variable of interest rates, the level of profit sharing, liquidity, inflation, the size of the company, and the growth of gross domestic product simultaneously significant influence on mudaraba deposits at Islamic Commercial Banking in Indonesia. while partially variable of the level of profit sharing, and the size of the company positivelly significant influence on mudaraba deposits at Islamic Commercial Banking in Indonesia, but interest rates, liquidity, inflation, and the growth of gross domestic product does not significant influence on mudaraba deposits at Islamic Commercial Banking in Indonesia.